PELATIHAN PENERAPAN KESELAMATAN DAN KESEHATAN KERJA KEPADA SISWA SEKOLAH MENENGAH KEJURUAN - Hasianna Nopina Situmorang; Banu Nursanni; Siti Ulgari (Universitas Negeri Medan, 2021)
Abstract Occupational health and safety (OHS) needs to be understood and applied in every job, including practice in laboratories and workshops that facilitate students to avoid accidents when using equipment and machines. Most of the learning activities during the Covid-19 pandemic were carried out at home, and therefore the insights about work safety must be instilled in students. This service activity aims to provide insight of OHS to Vocational High School (SMK) students through training. The activity was carried out at SMK Parulian 3 Medan. The OHS implementation training is conducted online using Zoom-meeting, which includes presenting the OHS material followed by interactive discussions. The training materials distributed were about the basics of OHS, personal protective equipment, and ergonomics. The training materials are needed by SMK students. Students' understanding of the application of OHS in the practical learning process increases so that there are no injuries or accidents. Students' awareness is formed to prioritize safety and security at work. The results of the evaluation show that the training process, the benefits of training, and the presenters have delivered the material well and can be accepted by students. It is necessary to carry out the continuity of OHS training activities directly to facilitate communication and discussion. Keywords: Training, Occupational Health and Safety, Covid-19, Personal Protective Equipment